Coronary artery bypass surgery in the UK, trends in activity and outcomes from a 15-year complete national series. (27th August 2021) - Ohri, Sunil K; Benedetto, Umberto; Luthra, Suvitesh; Grant, Stuart W; Goodwin, Andrew T; Trivedi, Uday; Kendall, Simon; Jenkins, David P
Abstract:  : OBJECTIVES: The aim of this study was to review the UK national trends in activity and outcome in coronary artery bypass graft (CABG) over a 15-year period (2002–2016). METHODS: Validated data collected (2002–2016) and uploaded to National Institute for Cardiovascular Outcomes Research were used to generate summary data from the National Adult Cardiac Surgery Audit Database for the analysis. Logistic European System of Cardiac Operative Risk Evaluation was used for risk stratification with recalibration applied for governance. Data were analysed by financial year and presented as numerical, categorical, %, mean and standard deviation where appropriate. Mortality was recorded as death in hospital at any time after index CABG operation. RESULTS: A total of 347 626 CABG procedures (282 883 isolated CABG, 61 109 CABG and valve and 4132 redo CABG) were recorded. Over this period annual activity reduced from 66.6% of workload to 41.7%. The mean age for isolated CABG was 65.7 years. The mean log European System of Cardiac Operative Risk Evaluation was 3.1, 5.9 and 23.2 for elective, urgent and emergency isolated CABG, respectively. There was a decline in the observed mortality for all procedures. Overall mortality for isolated CABG surgery is now 1.0% and only 0.6% for elective operations. CONCLUSIONS: Quality of care and risk-adjusted mortality rates have consistently improved over the last 15 years despite the increasing risk profile of patients. There have been a consistent decline in overall case volumes and a three-fold increase in elderly cases. Abstract : Society of Cardiothoracic Surgery (Great Britain and Ireland) (SCTS) was one of the first societies in the world to start reporting cardiac surgical outcome data in 1977 [1].